2011
DOI: 10.1182/blood-2010-11-321398
|View full text |Cite
|
Sign up to set email alerts
|

Platelet production and platelet destruction: assessing mechanisms of treatment effect in immune thrombocytopenia

Abstract: This study investigated the immature platelet fraction (IPF) in assessing treatment effects in immune thrombocytopenia (ITP). IPF was measured on the Sysmex XE2100 autoanalyzer. The mean absolute-IPF (A-IPF) was lower for ITP patients than for healthy controls (3.2 vs 7.8 ؋ 10 9 /L, P < .01), whereas IPF percentage was greater (29.2% vs 3.2%, P < .01).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
91
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 142 publications
(107 citation statements)
references
References 45 publications
5
91
1
4
Order By: Relevance
“…Remarkably, the coefficients of correlation differed between patients groups, from no correlation in healthy individuals to relatively high correlations in patients with thrombocytopenia due to peripheral destruction [66,67]. One study using the Sysmex XT-2000iV, which uses an identical method as XE-2100, demonstrated reasonable correlation between IPF and reference flow cytometry, albeit with a significant systematic bias [68].…”
Section: Comparison Of Reticulated and Immature Platelet Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, the coefficients of correlation differed between patients groups, from no correlation in healthy individuals to relatively high correlations in patients with thrombocytopenia due to peripheral destruction [66,67]. One study using the Sysmex XT-2000iV, which uses an identical method as XE-2100, demonstrated reasonable correlation between IPF and reference flow cytometry, albeit with a significant systematic bias [68].…”
Section: Comparison Of Reticulated and Immature Platelet Methodsmentioning
confidence: 99%
“…The absolute IPF (IPF#), the concentration of immature platelets (in 10 9 /L), might better reflect real-time platelet production in analogy with what absolute reticulocyte count does for erythropoietic activity [67]. There are indeed some reports indicating the usefulness of IPF# in neonatal infections [74], in chronic liver disease [51] and in differentiating acute ITP and from thrombocytopenia due to acute leukemia [75].…”
Section: Post-analytical Aspectsmentioning
confidence: 99%
“…12 On examination of bone marrow from ITP patients, Barsam et al found that both responders and non-responders to treatment with eltrombopag, a thrombopoietin receptor (TPO-R) agonist, showed a boost in MK proliferation without, however, the expected increase in platelet production in the nonresponders. 13 These observations may be explained by failure of eltrombopag to counter the antibody-induced defective proplatelet production in non-responding patients, suggesting that antiplatelet autoantibodies can have a direct, deleterious effect not only on MK production and maturation, but also on their crucial capacity to form proplatelets and consequently on platelet production.…”
Section: Introductionmentioning
confidence: 99%
“…24,26 Plasma glycocalicin was significantly lower in the mice fed the high-ALA diet (25 6 4 mg/mL compared with 53 6 27 mg/mL; Figure 1. Dietary ALA increases the platelet count but not their production.…”
Section: Tpo and Bone Marrow Macrophages Are Unchanged After A High-amentioning
confidence: 99%